2019
DOI: 10.1021/acs.organomet.8b00831
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Pentafulvene Titanium and Zirconium Complexes with Phosphorus Ylides: Stoichiometric Reactions and Catalytic Intramolecular Proton Shuttles

Abstract: The reaction of penta- and benzofulvene complexes of group 4 (M = Ti, Zr) with different phosphorus ylides is reported. Employing the bis­(η5:η1-penta­fulvene)­titanium complexes Ti1a and Ti1b, the reactions with the corresponding phosphorus ylides Y1–5 result in a spontaneous single C–H bond activation and metallocene ylide complexes Ti2a–e can be isolated in good yields. On the basis of these results, this reactivity pattern has been extended to the mono­(η5:η1-penta­fulvene) and -benzofulvene complexes Ti3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“… 5 , 38 40 Because the chemistry of bis(π–η 5 :σ–η 1 -pentafulvene)titanium complexes is characterized by a broad range of E–H activation and Ti–C functionalization reactions, 41 they are excellent precursors for the generation of bimetallic Ti/Fe complexes. 42 , 43 As we reported earlier, 44 both monofunctional and bifunctional transformations are possible depending on the substrate. Herein, we report novel bimetallic Ti/Fe complexes based on ferrocene aldehydes, ketones, alcohols and 1,1′-bis(phenylphosphine)ferrocene.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“… 5 , 38 40 Because the chemistry of bis(π–η 5 :σ–η 1 -pentafulvene)titanium complexes is characterized by a broad range of E–H activation and Ti–C functionalization reactions, 41 they are excellent precursors for the generation of bimetallic Ti/Fe complexes. 42 , 43 As we reported earlier, 44 both monofunctional and bifunctional transformations are possible depending on the substrate. Herein, we report novel bimetallic Ti/Fe complexes based on ferrocene aldehydes, ketones, alcohols and 1,1′-bis(phenylphosphine)ferrocene.…”
Section: Introductionmentioning
confidence: 65%
“…The synthesis and applications of heterobimetallic complexes are an ever-present topic in inorganic chemistry. Of particular interest is the incorporation of ferrocene derivatives into other metal complex frameworks. Since the discovery of ferrocene and its formerly unprecedented sandwich-structure, , many ferrocene derivatives have been reported. Because of the manifold derivatization options of the ferrocene framework, there is a huge number of polymetallic complexes containing ferrocenes which are linked with different bridges (C; N; O; P; S; , Se; , N,O ,, ). In the context of ferrocene-based titanium complexes, several studies have focused on clusters, electron-deficient catalysts , and redox-active compounds. , Because the chemistry of bis­(π–η 5 :σ–η 1 -pentafulvene)titanium complexes is characterized by a broad range of E–H activation and Ti–C functionalization reactions, they are excellent precursors for the generation of bimetallic Ti/Fe complexes. , As we reported earlier, both monofunctional and bifunctional transformations are possible depending on the substrate. Herein, we report novel bimetallic Ti/Fe complexes based on ferrocene aldehydes, ketones, alcohols and 1,1′-bis­(phenylphosphine)­ferrocene.…”
Section: Introductionmentioning
confidence: 93%
“…In this section, we will detail only mixed-metal supramolecular architectures including at least 2 titanium atoms. However, we can cite beforehand several examples of heteronuclear complexes (mostly binuclear) with only one Ti atom, the other metal or fragment being : an alkali metal; [169,210,211] Ni, Pd or Pt; [142,[212][213][214][215][216][217] Al; [218] Ga; [219] La; [220] Zr; [221] Mo; [222][223][224][225] Fe; [164] Rh; [226] or various metal carbonyls. [227][228][229][230][231] Most of the compounds resulting from multicomponent self-assembly processes detailed hereafter were highly-symmetric early-late heterobimetallic (ELHB) complexes; in general terms, such species display many interesting geometries and properties.…”
Section: Pentanuclear Complexes and Beyondmentioning
confidence: 99%
“…Recent investigations have shown that the employment of aliphatic-substituted nitriles can lead to subsequent 1,3-H-shifts when reacted with pentafulvene complexes. [26,30] To examine the influence of this substitution pattern on the synthesis of the targeted cationic complexes,asolutiono fc omplex 1 in nhexane was treated, in ad ropwise manner,w ith one equivalent of acetonitrile (L5)( 1.1 m in toluene)a tr oom temperature; this directly resulted in ac olor change of the reaction mixture from yellow-green to orange-red. After purification, the titanium enamine 7 was isolated in ag ood yield of 64 %, whichi s indeed the product of as ubsequent 1,3-H-shift after the insertion step (Scheme1 1).…”
Section: Reactivity Of Complex 2t Owards Acetonitrilementioning
confidence: 99%
“…The signals of the C q =CH 2 moiety show characteristic chemicalshifts in the 1 Ha nd 13 CNMR spectra at d 1 H = 3.60 and 4.09 ppm and d 13 C{ 1 H} = 81.0 (C q =CH 2 )a nd 176.7 ppm (C q = CH 2 ), respectively.T he other chemical shifts are in good agreement to titaniume namine complexes reported in the literature. [26,30] Reactivity of the titanium enaminec omplex 7towards B(C 6 F 5 ) 3…”
Section: Reactivity Of Complex 2t Owards Acetonitrilementioning
confidence: 99%